Effect of dexmedetomidine on postoperative cognitive function in patients with gastrointestinal cancer: a meta-analysis of randomized controlled trials - Xiaoxia Zheng; Yang Lan; Lesi Chen; Ruiming Du; Jiaxuan Wu (Frontiers in Neurology)
IntroductionThis meta-analysis was conducted to systematically evaluate the effects of dexmedetomidine (DEX) on mini-mental state examination (MMSE) scores and the incidence of postoperative cognitive dysfunction (POCD) in patients with gastrointestinal cancers (GICs) undergoing radical surgery (RS), by aggregating data from randomized controlled trials (RCTs).MethodsA comprehensive literature review was undertaken that encompassed seven databases from their inception until March 4, 2024. The quality of the studies was assessed using the Cochrane Collaboration tool to evaluate risk. Based on the heterogeneity determined through Cochran’s Q and I2 tests, either fixed-effect or random-effect models were employed to conduct the appropriate meta-analyses. Publication bias was assessed using the Egger test, while the stability of the results was evaluated through a one-by-one elimination method.ResultsA total of 12 studies involving 881 patients with GIC (440 patients treated with DEX and 441 patients receiving saline) were included in this meta-analysis. The overall quality of the included studies was deemed moderate. The application of a random-effect model indicated that DEX significantly elevated MMSE scores on postoperative days 1, 2, 3, and 7, albeit with considerable heterogeneity. Conversely, the fixed-effect model demonstrated a protective effect of DEX on the incidence of POCD. Nonetheless, subgroup analyses stratified by cancer type and surgical method did not identify the sources of heterogeneity. The Egger test revealed no evidence of publication bias across the included studies (p = 0.447). Sensitivity analyses further confirmed the robustness of the findings of this meta-analysis.DiscussionThe findings suggest that DEX exerts a protective effect on cognitive function in patients with GICs undergoing RS. Nevertheless, high-quality, large-scale RCTs are necessary to furnish more definitive evidence.